Development of a mobile application for second language acquisition - Hryhorenko, Y.; Marikutsa, U.; Matkovska, O. (Видавництво Львівської політехніки, 2016)
This paper focuses on the main concept of a mobile application for foreign language learning (English) for Ukrainians. The analysis of existing applications drawbacks has been carried out and ways to solve them have been offered. Different types of databases used for iOS mobile applications have been compared. Запропоновано основну концепцію мобільного додатка для укрїнських користувачів з вивчення іноземної мови (англійської). Недоліки існуючих додатків та запропоновано шляхи їх усунення. Порівняно різні типи баз даних, які використовуються для додатків на платформі iOS.
Розроблення мобільного додатка для вивчення іноземної мови
Keywords: second language acquisition; mobile application; part of speech; database; вивчення іноземної мови; мобільний додаток; платформа iOS; CoreData; Realm; база даних; 004.9